KOMBINASI STEGANOGRAFI BIT PLANE COMPLEXITY SEGMENTATION (BPCS) DAN KRIPTOGRAFI DATA ENCRYPTION STANDARD (DES) UNTUK PENYISIPAN PESAN TEKS PADA CITRA BITMAP GRAYSCALE 8 BIT - Paulus Klau; Derwin R Sin; Yelly Y Nabuasa (J-Icon : Jurnal Komputer dan Informatika, 2018)
Bit Plane Complexity Segmentation (BPCS) is steganography method that using uncapability of human’s vision in interpreting difficult biner form. Data Encryption Standard (DES) is cryptography algorhytm that is chiper block and changing data become blocks 64 bit and then using encryption key amount 56 bit. By combining steganography algorhytm and cryptography will increase quality of data security. In this research combination of BPCS and DES done by inserting text message into bitmap image, the increating text message restricted maximum 248 characteristic with the long of the key must 16 characteristic in hexsadecimal format. The result obtained by this system testing with image test about 30 images is the inserting text can be read again with the provision of using the same key for inserting process and reading text. This image of insertion result can’t stand to adding contrast operation (25%) and rotation (90 to the right, 90 to the left, 180) and cutting operation on the upper side dan left image, but if cutting on the lower side and right (image resolution > 100 piksel) the inserting text can be read again correctly. In image inserting result, will be found noise of the upper left side from image because these region is the initial region is inserted.